Replication analyses of four chromosomal deletions with schizophrenia via independent large‐scale meta‐analyses. Issue 8 (11th October 2016) - Chang, Hong; Li, Lingyi; Peng, Tao; Li, Ming; Gao, Lei; Xiao, Xiao
Abstract : Recent studies suggest that copy number variations (CNVs) are also involved in the genetic risk of schizophrenia. Using a Cochran–Mantel–Haenszel (CMH) adjusted meta‐analysis in 18, 497 schizophrenia patients and 25, 522 healthy controls from 14 independent samples, we conducted replication analyses of four chromosomal deletions at 1q21.1, 15q11.2, 15q13.3, and 22q11.2 Loci for their associations with schizophrenia. Only CNVs larger than 100 kb that had >50% reciprocal overlap with the canonical deletion chromosomal regions were considered. We successfully replicate the significant associations at 1q21.1 ( P value = 3.101 × 10 −7, odds ratio (OR) = 6.91), 15q13.3 ( P value = 4.771 × 10 −4, OR = 7.83), and 22q11.2 ( P value = 1.725 × 10 −5, OR = 9.21) deletions, although the effect sizes are relatively smaller than the original studies, which is not unexpected and adds further support for the involvement of these genetic lesions in the risk of schizophrenia. The 15q11.2 deletion, which shows higher frequency in healthy populations than the other three CNV loci, though is not significant in the present meta‐analysis ( P value = 0.1545, OR = 1.42), it shows the same direction of effects with previous studies. These results further confirm the genetic connections between rare CNVs and schizophrenia, and suggest the importance of adequate sample size in replication analyses for such risk loci with low frequency in general populations. © 2016 Wiley Periodicals, Inc.